Simultaneous High-performance Liquid Chromatography Determination of Non-nucleoside Reverse Transcriptase Inhibitor and Protease Inhibitors: Global Optimization Technique - Anitha, Ganna (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: An improved highly sensitive and robust reversed-phase high-performance liquid chromatography (HPLC) method for simultaneous determination of atazanavir (ATV), efavirenz (EFV), lopinavir (LPV), and ritonavir (RTV) along with carvedilol (IS) as an internal standard. Materials and Methods: Shimadzu HPLC system (Tokyo, Japan) containing a LC10AD and LC10 ADvp with UV detector (SPD-10A) and Thermo Hypersil C18 column was used in chromatography. The mobile phase comprising acetonitrile (ACN): 10 mM potassium di-hydrogen orthophosphate (55:45) delivered at a flow rate of 1 mL/min and monitored at a wavelength of 210 nm. The method developed was optimized using central composite design, a chemometric tool to optimize the factors (ACN, buffer concentration, and flow rate) effecting and interacting with the responses (k1, Rs2,1, Rs3,2, and tR5). Results and Discussion: The analysis time is 5.8 (<6 min). The method developed was validated according to ICH Q2 (R1) guidelines and confirmed the linearity, accuracy, precision, and specificity. The LOD and LOQ were found to be 1.065 and 3.227 ng/mL for ATV; 0.850 and 2.576 ng/mL for RTV; 0.744 and 2.255 ng/mL for LPV; and 0.315 and 0.955 ng/mL for EFV. Conclusion: The method developed is of highly sensitivity and aptness of the method was recognized by applying to three different combinations of commercially available formulations, confirmed applicability for routine analysis.